Analysis level of coordination abilities in children with impaired vision - Гложик [Glozhyk I.] Ірина Зинов’ївна; Якимец [Yakimets Z.] Зоряна Мирославівна (Slobozhanskyi Herald of Science and Sport, 2012)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> The paper analyzes the level of coordination skills in primary school children with visual impairments. Deviations in the visual analyzer in some way hinder the formation of motor skills, development of physical abilities. The largest gap found in terms of tests that reflect the level of ability for orientation in space and the ability to maintain a dynamic equilibrium. Development of coordination abilities in children of this category should be handled given the depth of the disease, age and psycho-emotional condition of the child. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>